Malignant Brenner tumor of the ovary: Case series and review of treatment strategies - Yingao Zhang; S. Allison Staley; Katherine Tucker; Leslie H. Clark (Elsevier, 2019)
Malignant Brenner tumor (MBTs) is a rare histological subtype of epithelial ovarian cancer, accounting for <0.05% of all ovarian neoplasms. As such, current evidence on the treatment of MBTs is predominantly limited to case studies and small case series. To add to existing literature, we performed a retrospective review of 10 cases of MBT diagnosed and treated at a single institution between 1999 and 2018.For the 10 cases included in our cohort, the median age was 64 and the median tumor stage was IIa/IIb. All patients underwent either a primary or interval debulking surgery and achieved an R0 resection per classifications set by the Union for International Cancer Control (UICC). Lymph node dissections were performed on 6 patients and found no evidence of positive nodal disease. 7 patients received platinum-based adjuvant chemotherapy and experienced a median progression-free survival (PFS) of 37 months. Recurrent disease was varied in terms of locoregional versus distant spread, and these patients had largely suboptimal responses to salvage chemotherapy with doxorubicin, gemcitabine, and eribulin. Sites of metastatic disease included the liver, lungs, bone, and brain.While there is no consensus for the optimal treatment of this rare disease, MBTs seem to respond well to adjuvant platinum-taxane treatment after complete surgical resection, consistent with the current management approach of other epithelial ovarian cancers. Recurrent disease is considerably more difficult to manage, and clinicians may consider a wider avenue of treatment options to include hormonal, biologic, and radiation therapies. Keywords: Malignant Brenner tumor, MBT, Ovarian carcinoma, Treatment, Review, Case series